A retrospective observational study comparing rescue medication use in children on combined versus separate long-acting β-agonists and corticosteroids. Issue 10 (23rd July 2010) - Elkout, H; McLay, J S; Simpson, C R; Helms, P J
Abstract : Background: Data on the efficacy and safety of long-acting β2-agonists (LABA) in children are limited, and current guidelines recommend that LABA always be used with inhaled corticosteroids (ICS). Objective: To compare asthma control, assessed by rescue medications use, in children prescribed LABA and ICS as a fixed-dose combination (LABA/ICS) or concurrently via separate inhalers (LABA+ICS). Methods: Retrospective observational study of asthma medication prescribed to children aged 0–18 years registered with 40 primary care practices for the years 2002–6. Asthma control, reflected by requirement for oral corticosteroids (OCS) and/or six or more short-acting β2-agonist (SABA) canisters per year, was assessed for children prescribed LABA/ICS or LABA+ICS. Results: 10 454 (8%) of all registered children received at least one prescription for asthma medication over the study period. Prescribing of LABA/ICS increased significantly, with a concomitant decrease in prescribing of LABA+ICS. Use of OCS increased by 60%, with the lowest use in children prescribed only SABA and highest use in those prescribed LABA. Children prescribed LABA/ICS were significantly less likely than those prescribed LABA+ICS to require OCS rescue therapy and or >6 SABA inhalers a year (OR 1.6; 95% CI 1.1 to 2.2; p=0.04 and OR 1.7; 95% CI 1.1 to 2.5; p=0.005, respectively, for the years 2005–6). Conclusions: The results of this retrospective observational study suggest that children prescribed fixed-dose LABA-and-ICS combination devices achieve better asthma control, as reflected in reduced requirements for SABA and reduced courses of OCS than equivalent doses in separate devices.